Intergenerational differences in dietary acculturation among Ghanaian immigrants living in New York City: a qualitative study. (24th September 2021) - Horlyck-Romanovsky, Margrethe F.; Huang, Terry T.-K.; Ahmed, Ramatu; Echeverria, Sandra E.; Wyka, Katarzyna; Leung, May May; Sumner, Anne E.; Fuster, Melissa
Abstract: Dietary acculturation may explain the increasing risk of diet-related diseases among African immigrants in the United States (US). We interviewed twenty-five Ghanaian immigrants (Youth n 13, Age (Mean ± sd ) 20 y ± 5⋅4, Parents ( n 6) and Grandparents ( n 6) age 58⋅7 ± 9⋅7) living in New York City (NYC) to (a) understand how cultural practices and the acculturation experience influence dietary patterns of Ghanaian immigrants and (b) identify intergenerational differences in dietary acculturation among Ghanaian youth, parents and grandparents. Dietary acculturation began in Ghana, continued in NYC and was perceived as a positive process. At the interpersonal level, parents encouraged youth to embrace school lunch and foods outside the home. In contrast, parents preferred home-cooked Ghanaian meals, yet busy schedules limited time for cooking and shared meals. At the community level, greater purchasing power in NYC led to increased calories, and youth welcomed individual choice as schools and fast food exposed them to new foods. Global forces facilitated nutrition transition in Ghana as fast and packaged foods became omnipresent in urban settings. Adults sought to maintain cultural foodways while facilitating dietary acculturation for youth. Both traditional and global diets evolved as youth and adults adopted new food and healthy social norms in the US.